Prioritizing Aspects of Disciplinary Behaviour in Private Islamic Elementary Schools Using Analytic Network Process (ANP) - Nesia Andriana; Endin Mujahidin; Arief Goeritno (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
Disciplinary behaviour in private Islamic elementary schools is shaped by multiple and interdependent factors involving educators, disciplinary methods, learning materials, facilities, and the broader school–family environment. However, existing approaches often identify disciplinary factors without establishing a clear priority order for strategic intervention. This study aims to identify, model, and prioritize the aspects of disciplinary behaviour that should receive greater attention in private Islamic elementary schools. The study employed the Analytic Network Process (ANP) to capture interdependencies and feedback among disciplinary aspects and to derive their relative priority weights through pairwise comparisons and super-matrix synthesis. The analysis involved four main clusters: Educator, Methods, Materials, and Facilities, together with disciplinary attitude outcomes. The results indicate that Educator was the most influential cluster, with a global priority weight of 0.39, followed by Methods (0.24), Materials (0.20), and Facilities (0.15). At the sub-criterion level, Parents (0.51), Teachers (0.29), Religious–moral Content (0.48), and Role Modelling (0.34) emerged as among the most influential elements. The priority outcomes were Obedient (0.33), Responsible (0.27), Respectful and Polite (0.21), and Not-Bullying (0.11). These findings indicate that disciplinary behaviour is primarily shaped by educator-related and value-based factors, particularly parental involvement, teacher influence, moral instruction, and role modelling. The study contributes an ANP-based priority framework that can support evidence-based intervention planning, resource allocation, and character-education strategies in private Islamic elementary schools.